Towards Peace and Sustainable Development in the North Rift Valley Region of Kenya (International Journal of Scientific Research and Management (IJSRM), 2016)
North Rift region is found the larger northern Kenya region. Most of the region is dry and is a home to pastoralist communities like the Pokot, Turkana and the Marakwet. Since the colonial era, the region has been marginalized by the successive governments. In fact, for the period that the British colonialists ruled Kenya, the northern frontier was closed to the general public. Pastoralists who live in this region depend mainly on scarce natural resources like pasture, water, natural vegetation and livestock. As such, there is pressure among the communities in terms of sharing thus leading to wars over boundaries, traditional migratory routes, and traditional grazing grounds. Northern Rift also has a very long boundary line with Uganda, Sudan and Ethiopia-countries that have at one time or another been affected by internal strife in the last thirty years leading to proliferation of small arms into the region. The sub counties in the North Rift have been marginalized for a long time hence illiteracy rates are very high and transport and communication is very poor. Since no meaningful investment has been put in place, there are high rates of unemployment. The pastoralists are forced by circumstances to lead sedentary lives hence their livelihoods and their fragile environment have deteriorated greatly. It is against this background that this study aimed at establishing ways of sustaining peace and development in the North Rift region. The study adopted the use of primary and secondary data collection. Primary data collection methods included survey questionnaires, interviews, focus group discussions and participatory observation. The purposive sampling method was employed in determining key informant interview respondents and focus group discussion participants. However, for key informants, there was also a snow-balling sampling approach. In terms of analysis, this exercise incorporated elements of the Theory of Change-based evaluation approach. The evaluation exercise integrated conflict sensitive methodologies in the survey and analysis of findings. Hence, the inquiry included questions aimed at understanding contextual dynamics, as well as sets of questions seeking to measure the extent of realization of project goals. Since peace building programs are not insulated from conflict blindness, conflict sensitive lens specifically the Do No Harm/Local Capacities for Peace framework was used to examine the impact of the intervention on the conflict dynamics. The SPSS software was used to analyze quantitative data. It was established that conflict mitigating and peace initiatives that have been employed in the North Rift inter alia tracking and arresting of perpetrators of conflicts by the government, creation and activation of community security and vigilante groups, strengthening of elders courts to arbitrate over conflict cases, recovery of stolen animals, introduction of alternative livelihoods, use of traditional early warning systems, inter community peace dialogues, peace committees, and inter community common grazing patterns. Communities have collaborated with NGOs for peace initiatives, relief services and long term development initiatives aimed at sustainable alternative livelihoods. World Vision Kenya has been at the forefront in this regard through a five year peace project, meant to bring peace among the warring communities.